(untitled) (Andamios, Revista de Investigación Social, 2009)
This article aims to get a general approximation to the so called welfare state crisis, and looks for identifying the institutional and structural components that sets this process. It will be analyzed also the German welfare state case, given that doing so could be very helpful in order to throw light and to visualize the specifics of the general debate. The main approach used in this article emphasizes the contractarian importance that historically has had the welfare state, which means, its contribution to both the social stability —in terms of democratic pluralism—, and the capitalist economic reproduction. In this sense, it is stated that the biggest challenges to the welfare state, current and prospective, relates to the link equality-full employment, the demographic transformation and the effects globalization.